Composição química e atividade biológica do extrato bruto etanólico do pólen de Corymbia Torelliana (F. Muell.) K.D. Hill & L.A.S. Johnson. (Myrtaceae) - Rebouças, Teresa Cristina Souza (2017)
Corymbia torelliana (F. Muell.) K.D. Hill & L.A.S. Johnson (Myrtaceae) is a pollinated species, easy to adapt, high resistance and therapeutic potential. Considering that pollen has demonstrated medicinal potential, this study aimed to evaluate the chemical composition and biological activity of the pollen of this species. The material was collected at Bahia Specialty Cellulose / Copener. The chemical composition (phenolic content, total flavonoids and phytochemical screening) was evaluated from the raw ethanolic pollen extract (EEP) and the biological tests of antioxidant activity, 2,2-diphenyl-1-picryl-hydrazila (DPPH) (Rota rod), analgesic activity (tests of abdominal contortions induced by acetic acid, formalin and hot plate) and anti-inflammatory (carrageenan-induced paw edema test) were analyzed using mice. The presence of terpenes, steroids and phenolic compounds was identified and the EEP presented 116.21 ± 7.80 mgEAG / g of phenolic compounds and 35.81 ± 8.37 mgEQ / g of flavonoids. In the antioxidant activity test, pollen was able to sequester DPPH with EC50 of 60.85 ± 4.70 μg / mL. As for the acute toxicity, no change was observed in the test used, nor was there any alteration in motor coordination in the Rota rod test. It was verified the presence of analgesic and anti-inflammatory activity of the EEP in the doses used (75, 150 and 300 mg / kg), and the dose of 75 mg / kg presented the best result. The results indicate an antioxidant, analgesic and anti-inflammatory potential for the EEP of this species, besides a possible peripheral and central activity.